2016 IEEE Conference on Control Applications (CCA) 2016
DOI: 10.1109/cca.2016.7587841
|View full text |Cite
|
Sign up to set email alerts
|

Icing detection for small fixed wing UAVs using inflight aerodynamic coefficient estimation

Abstract: We propose a method to detect icing of the airfoil of a fixed-wing Unmanned Aerial Vehicle by using an aerodynamic coefficient estimator and ambient temperature and humidity sensors. The estimator uses the information provided by a standard autopilot sensor suite consisting of an IMU, GNSS and a pitot-static tube to estimate lift coefficients as well as steady and turbulent wind velocities. These sensor inputs are fused within an Extended Kalman Filter using frequency separation and kinematic, aerodynamic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…() However, due to the large power consumption, fault/icing detection schemes with fast and accurate responses are needed for assuring high efficiency. The approaches recently applied to icing detection in aircrafts and UAVs include multiple models,() statistical methods, aerodynamic coefficient estimators, and environmental monitoring …”
Section: Introductionmentioning
confidence: 99%
“…() However, due to the large power consumption, fault/icing detection schemes with fast and accurate responses are needed for assuring high efficiency. The approaches recently applied to icing detection in aircrafts and UAVs include multiple models,() statistical methods, aerodynamic coefficient estimators, and environmental monitoring …”
Section: Introductionmentioning
confidence: 99%
“…Recently there have been research efforts to detect icing in flight [5], [13], [14], [16]. Test flights with real UAVs in icing conditions are risky and it is challenging to acquire reliable baseline data of the aerodynamic coefficients in icing.…”
Section: Introductionmentioning
confidence: 99%
“…whether it is affecting the wings, the tail, or all the UAV. Concerning the ISF, Seron et al (2015) and have suggested to employ a bank of observers, each of which corresponds to a quantised value of the ISF, and estimation algorithms that take into account the values taken by suitable signals have been also proposed (Wenz and Johansen, 2016). However, obtaining a detailed icing diagnosis, comprising information about the icing location, is still an open problem.…”
Section: Introductionmentioning
confidence: 99%